Microbiology, antioxidant, and antibacterial activity of sinom kombucha - Zubaidah, Elok; Dewi, Camelia Norosita; Yua, Ezza Selisa; Putri, Nazhifah Vitya (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2024)
Kombucha is a traditional drink made from a fermented sweet tea with a mixed culture known as a symbiotic culture of bacteria and yeast (or SCOBY). Although kombucha is usually made from black tea, nowadays, kombucha can be made in various variations such as sinom beverages. Sinom is a traditional Indonesian herbal drink originating from young tamarind leaves or sinom. In addition to tamarind leaves, sinom includes other ingredients such as sugar and turmeric. Turmeric contains curcumin, which is beneficial for health because it has the ability as an antioxidant, anti-inflammatory, antitumor, and lowering blood fat or cholesterol levels. Tamarind leaves contain chemical compounds of flavonoids, phenols, terpenoids, steroids/triterpenoids and are included in the group of plant extracts with antioxidant activity. These chemical compounds can be increased through the kombucha fermentation process. The concentration of turmeric rhizome  used in kombucha was 0.8% (w/v), while the tamarind leaves used were 0%, 0.2%, 0.4%, 0.6%, 0.8%, and 1% (w/v). Sinom kombucha fermented for 7 days. The analysis performed included total microbes, total lactic acid bacteria (LAB), pH, total sugar, total phenol, antioxidant activity, and antibacterial activity against S. aureus and E. Coli growth. The fermentation process and various tamarind leaf concentrations have significant effects in total microbes, total LAB, total sugar, total phenol, IC50. The antibacterial activity is affected by fermentation but not by the variations in tamarind leaf concentrations. The best tamarind leaves concentration of kombucha sinom beverages was at 0.6%, which has a pH value of 3.81, total sugar content of 7,58%, and total phenol content of 240.9 µg GAE/mL, IC50 value of 159.84 ppm, total microbial count 3.37 x 107 CFU/mL, total LAB of 4.63 x 105, antibacterial activity against E. coli of 3.1 mm, and antibacterial activity against S. aureus of 3.27 mm.